Pentingnya Pendidikan Kewirausahaan di Perguruan Tinggi - Siregar, Padrie Payung; Julmasita, Regina; Ananda, Syahla; Nurbaiti, Nurbaiti (Asatiza: Jurnal Pendidikan, 2023)
Entrepreneurship education in tertiary institutions has an important role in developing entrepreneurial potential and interest. This study aims to discuss the importance of entrepreneurship education in tertiary institutions through several key aspects. A qualitative study design with a literature study approach was chosen as the study model, while the analytical method used content analysis. The results of the analysis of the study show that entrepreneurship education is useful for equipping students with the knowledge and skills needed to start and manage a business; help create jobs by encouraging students to become entrepreneurs and create job opportunities; stimulate innovation by teaching students to think creatively; identify business opportunities, and develop new ideas. In order to optimize the benefits of entrepreneurship education, universities need to overcome challenges such as relevant curriculum design, limited resources, collaboration with the business world, practical skill development, and response to changing business trends.